Parenting Predictors of Delay Inhibition in Socioeconomically Disadvantaged Preschoolers. Issue 5 (September 2016) - Merz, Emily C.; Landry, Susan H.; Zucker, Tricia A.; Barnes, Marcia A.; Assel, Michael; Taylor, Heather B.; Lonigan, Christopher J.; Phillips, Beth M.; Clancy‐Menchetti, Jeanine; Eisenberg, Nancy; Spinrad, Tracy L.; Valiente, Carlos; et al.
Abstract : This study examined longitudinal associations between specific parenting factors and delay inhibition in socioeconomically disadvantaged preschoolers. At Time 1, parents and 2‐ to 4‐year‐old children (mean age = 3.21 years; N = 247) participated in a videotaped parent–child free play session, and children completed delay inhibition tasks (gift delay‐wrap, gift delay‐bow, and snack delay tasks). Three months later, at Time 2, children completed the same set of tasks. Parental responsiveness was coded from the parent–child free play sessions, and parental directive language was coded from transcripts of a subset of 127 of these sessions. Structural equation modelling was used, and covariates included age, gender, language skills, parental education, and Time 1 delay inhibition. Results indicated that in separate models, Time 1 parental directive language was significantly negatively associated with Time 2 delay inhibition, and Time 1 parental responsiveness was significantly positively associated with Time 2 delay inhibition. When these parenting factors were entered simultaneously, Time 1 parental directive language significantly predicted Time 2 delay inhibition whereas Time 1 parental responsiveness was no longer significant. Findings suggest that parental language that modulates the amount of autonomy allotted the child may be an important predictor of early delay inhibition skills. Copyright © 2015 John Wiley & Sons, Ltd.